Dampak Beban Gempa Terhadap Biaya Struktur Kolom Rumah Tinggal Bertingkat - Budiman, Rizki (Universitas Muhammadiyah Palembang, 2025)
This study analyzes the impact of earthquake loads, represented by Peak Ground Acceleration (PGA), on the construction cost of reinforced concrete columns in two-story residential buildings in Indonesia. Using a numerical simulation approach, the research evaluates four PGA scenarios (0.0155g to 0.7172g) to assess their influence on column design specifications (dimensions, reinforcement) and associated costs. Results indicate that higher PGA values significantly increase internal forces, particularly bending moments (Mx and My), which rise up to 4.1 times at PGA 0.7172g compared to the lowest PGA (0.0155g). Axial forces show a more moderate increase. To resist these forces, column dimensions and reinforcement requirements escalate, with material upgrades (e.g., BJTS-420 steel) necessary for high-risk zones. Cost analysis reveals a near-linear relationship between PGA and construction costs, with a 1.94-fold increase at PGA 0.7172g, driven primarily by material expenses (63% of total costs). The study highlights the economic implications of seismic design, demonstrating that while higher PGA demands elevate initial costs, they are justified by enhanced structural safety and long-term risk reduction. These findings underscore the importance of performance-based design to optimize material use without compromising seismic resilience, providing actionable insights for policymakers and engineers in earthquake-prone regions.